2013
DOI: 10.1016/j.neulet.2013.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cholinergic phenotype in septohippocampal projection neurons: Relation to brain versus peripheral IL-2 deficiency

Abstract: In the peripheral immune system, IL-2 is essential for immune homeostasis, normal T regulatory cell function, and self-tolerance. IL-2 knockout (IL-2KO) mice develop spontaneous autoimmunity characterized by increased T cell trafficking to multiple organs. The IL-2 gene is also expressed in the brain, and in vitro studies have shown that IL-2 is a potent modulator of acetylcholine release from septohippocampal neurons and exerts trophic effects on septal neurons in culture. We previously described the apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Our hypothesis that alterations in learning acquisition in IL-2KO would be associated largely with the loss of brain-derived IL-2 was not confirmed in Experiment 1, as the congenic IL-2KO/SCID and WT/SCID littermates did not differ in Morris water-maze performance. That hypothesis was based on a series of studies from our lab where we found that there is a marked phenotypic loss of the ChAT-positive neurons in the MS/vDB of IL-2KO mice that occurs between weaning and adulthood that results from the absence of brain-derived IL-2 during development [ 16 , 17 , 19 ]. Although the loss of brain-derived IL-2 in IL-2KO/SCID mice was not associated with alterations in spatial learning in the Morris water-maze, the results of Experiment 2 suggest that autoimmunity associated with peripheral IL-2 gene deletion altered learning acquisition in adult IL-2KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our hypothesis that alterations in learning acquisition in IL-2KO would be associated largely with the loss of brain-derived IL-2 was not confirmed in Experiment 1, as the congenic IL-2KO/SCID and WT/SCID littermates did not differ in Morris water-maze performance. That hypothesis was based on a series of studies from our lab where we found that there is a marked phenotypic loss of the ChAT-positive neurons in the MS/vDB of IL-2KO mice that occurs between weaning and adulthood that results from the absence of brain-derived IL-2 during development [ 16 , 17 , 19 ]. Although the loss of brain-derived IL-2 in IL-2KO/SCID mice was not associated with alterations in spatial learning in the Morris water-maze, the results of Experiment 2 suggest that autoimmunity associated with peripheral IL-2 gene deletion altered learning acquisition in adult IL-2KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has shown previously that IL-2KO mice have altered learning acquisition in the Morris water-maze and related septohippocampal changes including fewer infrapyramidal granule cells, reductions in hippocampal infrapyramidal mossy fiber length, alterations in neurotrophin levels, and marked phenotypic loss of choline acetyltransferase (ChAT)-positive neurons in the medial septum/vertical diagonal band of Broca (MS/vDB) that occurs between weaning and adulthood [ 16 19 ]. Moreover, we have found that loss of brain IL-2 gene expression results in dysregulation of the brain’s endogenous neuroimmunological milieu (e.g., increasing chemokines that attract autoreactive T cells into the brain), and may be involved in initiating processes that lead to the progression of CNS autoimmunity [ 6 , 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also detected modest levels of GFP expression from a subset of cells in the subiculum, the main output structure of the hippocampus, that projects back to the septal nuclei (in addition to other GFP-positive regions including the prefrontal cortex, hypothalamus, mammillary nuclei, entorhinal cortex, and amygdala). Previously, we showed the effects of brain-derived IL-2 deficiency on cholinergic phenotype and neurotrophin expression in the septohippocampal system of IL-2KO mice [ 25 , 26 ]. In addition to the neuropathology in the septum and hippocampus, we have detected changes in several measures of behavior.…”
Section: Discussionmentioning
confidence: 99%